Soil Organic Carbon Sequestration Rates under Crop Sequence Diversity, Bio‐Covers, and No‐Tillage. Issue 5 (25th September 2014) - Ashworth, Amanda J.; Allen, Fred L.; Wight, Jason P.; Saxton, Arnold M.; Tyler, Don D.; Sams, Carl E.
Abstract : Climate change may be mitigated through soil organic C (SOC) storage under no‐tillage; however, crop management influences on SOC are not well defined in all systems. Our objective was to compare long‐term C fluxes under two no‐tillage sites at Research and Education Centers in Milan (RECM) on Oxyaquic Fragiudalfs and at Middle Tennessee (MTREC) on a Typic Paleudalf in a split‐block design with four replications. The whole‐block was cropping sequences of corn ( Zea mays L.), soybeans [ Glycine max (L.) Merr.], and cotton ( Gossypium hirsutum L.) with split‐block bio‐cover treatments of winter wheat ( Triticum aestivum L.), hairy vetch [ Vicia villosa Roth subsp. villosa ], poultry litter, and a fallow control. The same sequences were performed at MTREC without cotton. Soil C flux was calculated at surfaces (0–5 cm) and subsurfaces (5–15 cm) during Year 0, 2, 4, and 8. During the first 2 yr, C losses occurred in all treatments and locations (1.40 and 1.20 Mg ha −1 at RECM and MTREC, respectively), with stabilization initiating by Year 4. By Year 8, sequences with high frequencies of soybean and greater temporal complexity gained more surface SOC. Poultry litter bio‐covers gained more surface SOC compared to wheat, vetch, and fallow bio‐covers ( P < 0.05). After 8 yr, surface SOC surpassed initial levels (9.20 and 8.79 Mg ha −1 ), with mean gains of 1.33 and 1.16 Mg C ha −1 at RECM and MTREC, respectively. Losses occurred in subsoils at MTREC and RECM, but by Year 8 several treatments had recovered to near baseline levels. Results suggest surface C storage may be enhanced by crop sequence diversity combined with poultry litter bio‐covers in no‐till systems, whereas subsurface levels may require more time.